Interplay between mitochondrial dysfunction and lysosomal storage: challenges in genetic metabolic muscle diseases with a focus on infantile onset Pompe disease - Zhang, Mengjiao; Niu, Jiechao; Xu, Mengmeng; Wei, Erhu; Liu, Peng; Sheng, Guangyao (Frontiers in Cardiovascular Medicine, 2024)
Congenital metabolic defects are among the common causes of pediatric cardiomyopathy, a condition where the heart's metabolic activity is high and any metabolic disorder can easily lead to cardiac changes. These manifest as hypertrophic or dilated cardiomyopathies, leading to heart failure, cardiogenic shock, or even sudden death, accounting for 5% of pediatric cardiomyopathy causes. This category includes diseases like glycogen storage disease, lysosomal storage disorders, mitochondrial diseases, and fatty acid oxidation disorders. Among them, glycogen storage disease is a common metabolic disease causing cardiac hypertrophy in children. Infantile-Onset Pompe Disease (IOPD), for instance, can lead to progressive worsening of myocardial hypertrophy, reduced ventricular volume, and heart failure. This disease is caused by a deficiency or absence of acid alpha-glucosidase (GAA), leading to abnormal accumulation of glycogen in cells. Specific blood and urine metabolic screening and genetic testing are common diagnostic strategies for these diseases. Symptomatic treatment through specific dietary supplements or enzyme replacement can improve the accumulation of abnormal metabolic products, thus alleviating clinical symptoms. This study aims to comprehensively analyze the clinical characteristics, diagnostic challenges, and current treatment strategies of infantile Pompe disease (PD), in hopes of providing references for future research and clinical practice.